La paideia del príncipe y la ideología helenística de la realeza - Alonso Troncoso, VÍCTOR (Gerión. Revista de Historia Antigua, 2006)
This paper is not a study about the possible contents of royal education, nor about the princes’ teachers. It does not primarily deal with the kings’ cultural politics in the Hellenistic age either. Our main concern here is to asses the importance of paideia as an element of the ideology of Hellenistic kingship. The main question to be answered is this: In which texts and in which terms is the relationship between paideia and basileia made explicit? Contemporary sources bore direct witness to this relationship and will thereby constitute the basis for our analysis. Three dynasties will be considered preferentially, the Ptolemies, the Attalids and the Antigonids, because of the quality of the sources about them.*